2023
DOI: 10.2147/ijgm.s389216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emergency Percutaneous Coronary Intervention Combined with Sacubitril and Valsartan on the Cardiac Prognosis in Patients with Acute Myocardial Infarction

Abstract: Purpose This study aimed to investigate the effect of emergency percutaneous coronary intervention (PCI) combined with sacubitril-valsartan (Entresto) on the cardiac prognosis in patients with acute myocardial infarction (AMI). Patients and Methods A total of 78 AMI patients who were treated in our hospital between January 2020 and September 2021 were included and randomly divided into treatment group and control group (n=39 per group). In the control group, patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…A total of 129 articles were initially retrieved. The information on the articles was imported into the EndNote X9.1 software, and after duplicate checking and screening, 10 articles were finally included [8][9][10][11][12][13][14][15][16][17]. The screening process and results of the articles are shown in Fig.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 129 articles were initially retrieved. The information on the articles was imported into the EndNote X9.1 software, and after duplicate checking and screening, 10 articles were finally included [8][9][10][11][12][13][14][15][16][17]. The screening process and results of the articles are shown in Fig.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…The methodological quality of the studies included in this analysis was assessed using RevMan 5.3. Among the 10 studies analyzed, 8 studies [9][10][11][12][13][14][15][16] were described as randomized, 1 study [8] was randomized double-blind, and 1 study [17] was randomized using envelope method. The risk assessment of bias included in the study is shown in Figs.…”
Section: Risk Of Biasmentioning
confidence: 99%